Legal Review of Legal Protection for Bond Holding Investors (Case Study at Bank X) - Willy Tanjaya (Faculty of Law, Universitas Pekalongan, 2024)
The Capital Market has a quite promising role in the development of the Indonesian economy, namely as a source of financing for the business world and an investment vehicle for the community. One form of investment activity offered to investors in the capital market is bonds. Investing in bonds is not without risk, because the bond issuer may fail to pay its obligations. To protect investors from this risk of default, in the bond issuance process, the issuer involves a third party (trustee) who represents the interests of investors. This research is a normative-empirical juridical type. This research is descriptive. The data in this study consists of primary data and secondary data. The data collection instruments in this study are divided into two, namely primary and secondary data. Primary data was collected using the interview method, while secondary data collection used documentation studies. This study uses qualitative analysis techniques, because the data obtained is mostly qualitative data. The objective of this study is to analyze the application of legal protection for bondholder investors against the risk of default.